Morning glories (2010), volume 9 ebook - Spencer, Nick (Morning Glories (2010), 2016)
Collecting the "Assembly" arc! Everything converges as Casey challenges the Academy's favorite in the Student Council elections, while Ike and Jake confront the demons in their pasts. The run-up to the explosive Season 2 finale begins here! Collects MORNING GLORIES #43-46.. Author: Nick Spencer. Illustrator: Joe Eisma . 2015 Nick Spencer & Joe Eisma.